PUBLIC SERVICES RESPONSIBILITY: HANDLING OF UNDOCUMENTED CITIZENS BY SANTIAGO SUB-GOVERNMENT IN SANGIHE ISLAND REGENCY - Katerina Bataha; Diana Hertati; Dandi Darmadi; Binti Azizatun Nafi’ah (DIA: Jurnal Administrasi Publik, 2021)
The government of Santiago Sub-District, Tahuna District has found that there are undocumented citizens who have been working and living in the Santiago Sub-District, Tahuna District for years. Refers to the 1945 Constitution Article 26 Paragraph 2, undocumented citizens who have worked and live in the area of the Santiago Sub-District are citizens who are entitled to public services as described in Law Number 25 of 2009 Article 1. This study aims to determine the responsiveness of the Santiago Sub-District government in handling undocumented citizens in the Santiago Sub-District, Sangihe Islands Regency. The type of research used is qualitative with a case study approach to explain the phenomenon related to the responsiveness of the Santiago Sub-District government in dealing with the problem of undocumented citizens by using 3 responsiveness indicators, namely the ability to respond, speed of service, and accuracy of serving. The results showed that the responsiveness of the Santiago Sub-District government in handling undocumented citizens was going well and was right on target.